The Effectiveness of Personalized Nursing on Quality of Life in Cardiovascular Disease Patients: A Systematic Review and Meta-analysis. (16th January 2023) - Yang, Min; Ta, Na; Bai, Xue; Wei, Chengxi; Sun, Chengshan; Han, Chunjuan
Abstract : Aims . This study aimed to examine the potential effectiveness of personalized nursing interventions on improving the heart-related quality of life of patients with CVDs versus an usual care. Design . A systematic review and meta-analysis. Data Sources . The study researched the article between January 2011 and December 2021 from four electronic databases: PubMed, Embase, Cochrane library, and Web of Science. Review Methods . Randomized controlled trials (RCTs) related to personalized nursing in CVDs population were included. The main variables were analyzed by standardized mean differences with 95% confidence intervals and heterogeneity was used by the I 2 test and P value. Results . Of 734 studies, fourteen articles were eligible for this study. Personalized nursing significantly improved the quality of life [SMD = 0.39, 95% CI (0.29, 0.49)] with obvious heterogeneity (P = 0.000, I 2  = 66.1%) which needs to be further subgroup analyzed. The nurse-led intervention was considered the main-related effect to influence the heterogeneity with value of 0.39 (I2 = 66.1%, P = 0.000 ; Group 1: I2 = 48.4%, P = 0.071, and Group 2: I2 = 0.0%, . In addition, related results of athletic ability and mental health and follow-up and education in the intervention had higher level of quality of life compared to the control group [SMD = 0.27, 95% CI (0.10, 0.44); SMD = 0.21, 95% CI (0.04, 0.37); SMD = 0.39, 95% CI (0.29, 0.49) and SMD = 0.28, 95% CI (0.11, 0.44)]. Conclusion . Effectiveness studies of personalized care focus on more relevant outcomes have higher health outcomes, whereas evidence of the effectiveness of personalized nursing approach is still limited. Therefore, more and more high-quality RCT are needed.